Fetal circulatory redistribution in normal and intra-uterine growth restriction (IUGR) pregnancies by volume blood flow (VBF). (18th April 2012) - Mullins, E; Damodaram, MS; Story, L; Prior, T; Kumar, S
Abstract : Introduction: A number of studies have reported that 'sparing' or redistribution occurs in various vascular beds in IUGR. We took a global approach to assessing this redistribution using VBF. Method: Women booking at Queen Charlotte's & Chelsea Hospital were recruited. Serial scans for growth, vessel diameter (VD) and power Doppler studies of the ascending aorta (AA), internal carotid (IC), middle cerebral artery (MCA), aortic isthmus (AI), descending aorta (dA) renal artery (RA) femoral artery (FA) and umbilical artery (UA), were performed at 24, 28, 32 and 36 weeks or as indicated. VBF was calculated and adjusted for estimated fetal weight (EFW). Statistics with SPSS.v.19. Results: VBF increased in all arteries with gestation in normal pregnancies. Increased VBF/kg was seen in the AA in IUGR from 24-32 weeks (p<0.001). Increased VBF and VBF/kg were seen in IUGR the IC and MCA from 24-36 weeks (p<0.001). Decreased VBF was evident in IUGR in the AI at 28-36 weeks (p=0.01), dA at 28 and 32 weeks and FA at 28 weeks (p=0.03). In IUGR there was increased VBF and VBF/kg in the RA (p=0.04, p<0.001 respectively) and increased VBF/kg in the UA from 24-32 weeks. Discussion: 'Brain sparing' was demonstrated with VBF and/or VBF/kg increased in the AA, IC and MCA. There was concurrent 'sparing' of the RA and UA. Decreased flow is seen in the AI, dA and FA indicating diversion of circulation to branches supplying organs essential for survival, the brain, kidneys and placenta. This was more marked in early-onset IUGR.